Task-dependent neuromuscular adaptations in low back pain: a controlled experimental study - Ducas, Julien; Marineau, Emile; Abboud, Jacques (Frontiers in Human Neuroscience, 2024)
Introduction This study investigated the variability in lumbar neuromuscular adaptations to pain, the task dependency of pain adaptations and the effect of these adaptations on motor performance. Methods Twenty-four healthy participants performed isometric back extension contractions at 45° and 90° trunk flexion under pain-free and experimental low back pain conditions induced by electrical stimulation. High-density surface electromyography recorded lumbar muscle activation strategies, and force steadiness was measured using a load cell. Results While considerable variability in neuromuscular adaptations to lumbar pain was observed among participants, consistent patterns were found between tasks. In the 90° trunk flexion position, both sides exhibited greater magnitudes of pain adaptations for muscle activity redistribution in the mediolateral axis (p < 0.05, 86% increase) and muscle activity amplitude (p < 0.001, 183% increase) compared to the 45° trunk flexion position. A significant negative correlation was found between the magnitude of the mediolateral spatial redistribution of muscle activity and force steadiness on the left side (p = 0.045). Discussion These findings highlight the intricate and task-dependent nature of neuromuscular adaptations to pain within lumbar muscles, and points toward a potential trade-off between pain adaptations and performance.